Respiration under monotonuous hypokinetic conditions. First results - Lopotová, Martina; Otáhal, Stanislav; Smrčka, Pavel; Lopot, František; Sieger, Ladislav (Acta Universitatis Carolinae. Kinanthropologica, 2011)
The aim of our work is to assess the influence of tiredness on changes in respiratory parameters during monotonous hypokinetic loading. In the current phase of the work, we are looking for the answer to the question whether these changes can predict upcoming tiredness or indicate only. On the pilot measurement, three males and two females aged 25-35 were participated. To capture the transition states of consciousness, a measurement was proposed in two modes: active vs. tired individual. For recording of breathing, two chest straps and a spiroergometer were used. Symptoms of tiredness were monitored by ECG and EEG. The course of the experiment was recorded by a video camera. Currently, we process the obtained data and from actual results, we can confirm that the upcomming tiredness can be with certainty found in the respiratory curves. The upcoming tiredness assessed merely by subjective analysis of videos was apparently associated with changes in breathing pattern. Quite a clear answer, if changes of the breathing pattern has predictive or indicative character, we will obtain from further comparison the respiratory curves with results of analyses of EEG and ECG signals, which are currently under processing.
Keywords: Video Recording; elektrokardiografie; elektroencefalografie; Humans; Respiration; lidé; financování organizované; Electrocardiography; Human Experimentation; pohybová aktivita; Hypokinesia; statistika jako téma; Financing, Organized; dýchací soustava; experimenty na lidech; spirometrie; Fatigue; Respiratory Mechanics; Electroencephalography; Motor Activity; Statistics as Topic; únava; Respiratory System; dýchání; monotomie; Adult; dospělí; Spirometry; hypokinetická zátěž; hypokineze; audiovizuální záznam; mechanika dýchání; Pilot Projects; pilotní projekty